SYNTHESIS, CHARACTERIZATION, AND ANTIBACTERIAL STUDY OF ZINC OXIDE-GRAPHENE NANOCOMPOSITES - Kumar, Harish; Kumari, Manisha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: A novel facile synthesis of zinc oxide (ZnO) and zinc-graphene oxide nanocomposites (ZnGONC) was achieved by modified sol-geltechnique for their pharmaceutical and therapeutic use. Materials and Methods: Spherical, crystalline, defect-free Zinc oxide nanoparticles (ZnO NPs) with diameter 70-90 nm were synthesized by modifiedsol-gel technique. Reduced graphene oxide was synthesized by modified Hummers method. ZnGONC were synthesized by in situ method. The crystallinenature, size, shape, and dimensions of the NPs, graphene oxide, and nanocomposites were studied by X-ray diffraction method. Transmission electronmicroscopy analysis was carried out to examine the morphology of NPs and nanocomposites. Results: Fourier transform infrared spectroscopy analysis confirms that the ZnO NPs are surrounded by oxygen and silicon atoms. Antibacterialactivity of ZnO NPs and ZnGONC was investigated against Gram-positive and Gram-negative bacteria. Zone of inhibition shown by ZnO NPs andZnGONC was found to be higher than six investigated standard antibiotics. Conclusion: Synthesized ZnO NPs and nanocomposites can be used as antibacterial agents. This eco-friendly method of synthesis of ZnO NPs andZnGONC could be a viable solution for industrial applications in the future and therapeutic needs.